Aplikasi Pembelajaran Bahasa Inggris pada TK Terpadu Padre Annibale School Maumere Berbasis Mobile - Claudia Betruchy Bada; Gerfasius Take Piran; Maria Yunita; Theresia Wihelmina Mado (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
This study aims to develop a mobile-based English learning application that can support the teaching process for both teachers and students in Kindergarten (TK). The subjects of this study are the students of Padre Annibale School for the 2025-2026 academic year. The background of this research is the limited use of learning media that cannot actively involve students. Additionally, many children in the millennial era are more attracted to electronic media, especially mobile phones, which presents a challenge in the learning process. The tendency for children to spend more time on mobile phones rather than reading books or listening to the teacher’s instruction can be seen as an opportunity to introduce technology-based learning media. With the presence of learning applications on mobile phones, students can access educational information anytime, both at school and at home. This application is designed to provide ease in obtaining English learning materials that meet the needs of students, as well as assist teachers in enriching their teaching methods. Through this approach, it is hoped that the teaching and learning process can be more interactive and engaging for students, while also supporting the integration of technology in education.